Harnessing legal system complexity for radical shifts to sustainability - Soininen, Niko; Ruhl, J. B.; Garmestani, Ahjond; Vesa, Seita; Kim, Rakhyun E.; Jalonen, Harri; Uusikylä, Petri; Kalimo, Harri; Keskinen, Marko; Huitema, Dave; Huhta, Kaisa; Belinskij, Antti; et al. (Springer, 2026)
Legal systems play a central role in enabling or constraining radical shifts to sustainability. We argue that the role of law in such shifts requires a reset, focusing more on strategically targeted nodes of the legal system rather than relying on major legislative reform. We develop a conceptual framework for identifying powerful changes to existing law that can trigger system-wide effects. We bridge computational network analysis with qualitative legal expertise to provide a methodological frame for identifying and interpreting the strategic legal changes and propose a framework for regulatory impact assessment to fit the frame.
Keywords: sustainability; complexity; legal systems; law; society; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|